THE PANDEMIC'S IMPACT ON THE GLOBAL INSURANCE INDUSTRY - Zakirkhodzhaeva Sh. A. (International Journal on Economics, Finance and Sustainable Development, 2021)
This article discusses the detrimental effects of a pandemic on the global and domestic insurance markets, as well as forecasts of future issues and recommendations for the development of the insurance industry during a pandemic.